Morfología del linfocentro cervical superficial de la llama (Lama glama) - Gauna Añasco, L. (2005)
The superficial cervical lymph center of the llama was studied trough macroscopic dissections and light microscopy, offering scientific bases about lymph drainage from anatomical regions which belong to the forelimb with importance for inspecting meat. The thoracic limbs were injected with modified Gerota?s mass; they were fixed by using a 10% buffered formalin solution. For light microscopy traditional methods were used. The afferent lymph vessels come from forefoot, antebrachial, brachial regions. The lymph nodes have flat surface and are smaller than those of other species. They have not a characteristic pattern of cortex, paracortex and medulla. Anyway they present lymph nodules, dense anodular lymphatic and diffuse lymphatic tissues distributed through the primary and secondary lymph nodules. The capsule does not present smooth muscle fibres and the peritrabecular sinuses are surrounded by diffuse limphatic tissue.